Dietaries studies--a family of six - Cooley, Ruth (My University, 1906)
Introduction: This is a farmers family consisting of four men and two women, all in good healthy condition. The four children attend college and do work enough at home to keep their appetites good. The studies were continued through the month of April 1906. The amount of food used and the amount wasted at each meal was weighed, and the cost of all material noted. Now at the close of the month we are able to determine the cost of living for the month and the total amount of material used—and the calorie and nutritive ratio of each meal.
Citation: Cooley, Ruth. Dietaries studies--a family of six. Senior thesis, Kansas State Agricultural College, 1906.
Morse Department of Special Collections
Keywords: Diet; Nutrition; Cost of Living; Theses; Manuscripts (documents)